Evolution Logic and Comparative Advantage of China’s Power System Reform—A Comparative Study on Transmission Management Between China and the United States - Wu, Wei-ping; Zeng, Wei-kang; Lu, Li-fan; Chen, Zi-gui (Frontiers in Energy Research, 2021)
This paper examines the differences of power systems between China and the United States from the perspective of transmission management, and finally summarizes the institutional advantages of China's power system reform. The research shows that there are significant operation and supervision differences between China and the United States in transmission management. China has always maintained a unified management in transmission management, while the United States has adopted a decentralized management model in transmission. The implementation of centralized unified management in transmission links can not only ensure the timely and effective allocation of national power energy, but also be helpful to concentrate all kinds of resources to develop large-scale power projects.